2017
DOI: 10.1038/emm.2017.122
|View full text |Cite
|
Sign up to set email alerts
|

Enteric dysbiosis-linked gut barrier disruption triggers early renal injury induced by chronic high salt feeding in mice

Abstract: Chronic high-salt diet-associated renal injury is a key risk factor for the development of hypertension. However, the mechanism by which salt triggers kidney damage is poorly understood. Our study investigated how high salt (HS) intake triggers early renal injury by considering the ‘gut-kidney axis’. We fed mice 2% NaCl in drinking water continuously for 8 weeks to induce early renal injury. We found that the ‘quantitative’ and ‘qualitative’ levels of the intestinal microflora were significantly altered after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 42 publications
3
70
0
Order By: Relevance
“…In the past decade, the gut microbiota has been proven to modulate injury responses in a number of organs remote from the gastrointestinal tract, especially in liver . Microbial metabolites are believed to be the main mediators for this progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, the gut microbiota has been proven to modulate injury responses in a number of organs remote from the gastrointestinal tract, especially in liver . Microbial metabolites are believed to be the main mediators for this progression.…”
mentioning
confidence: 99%
“…In the past decade, the gut microbiota has been proven to modulate injury responses in a number of organs remote from the gastrointestinal tract, especially in liver. (10)(11)(12)(13)(14) Microbial metabolites are believed to be the main mediators for this progression. We previously found that gut bacteria-derived saturated fatty acids exerted protective effects against alcohol-induced liver injury.…”
mentioning
confidence: 99%
“…Any factors that influence the intestinal microenvironment likely interrupt the balance in gut microbiota, ultimately leading to changes in the gut microbiome. For example, high choline intake elevates the level of blood trimethylamine oxide (TMAO), a metabolic factor that promotes cordial hypertrophy and ultimately increases the incidence of various cardiovascular-and cerebrovascular-related diseases [5][6][7][8][9], while even changes in diet can change the gut miceobiome [10][11][12]. All these factors can change the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, enteric microbiota dysbiosis and genetic abnormalities led to disruption of the intestinal barrier, thus triggering early kidney injury in mice [13]. Moreover, Thompson et al…”
Section: Introductionmentioning
confidence: 99%